Mixed-model moving assembly line material placement optimization for a shorter time-dependent worker walking time - Helmut A. Sedding (Journal of Scheduling, 2023)
Car mass production commonly involves a moving assembly line that mixes several car models. This requires plenty of material supplies at the line side, but available space is scarce. Thus, material is placed apart from ideal positions. Then, picking it up involves walking along the line. This time is non-productive and can encompass 10–15% of total production time. Thus, it is important to estimate and minimize it during production planning. However, the calculations are difficult because the conveyor continuously moves. Therefore, most literature bounds walking time by a constant, but this discards valuable potential. To better approximate it, we use a time-dependent V-shaped function. A comparison indicates that for a majority of instances, constant walking time estimates of 95% confidence are at least 51% higher. Then, we introduce a model to optimize material positions such that the model-mix walking time is minimized. This poses an NP-hard sequencing problem with a recursive and nonlinear objective function. Our key discovery is a lower bound on the objective of partial solutions, established by a Lagrangian relaxation that can be solved in quadratic time. Resulting branch and bound based algorithms allow to quickly and reliably optimize up to the largest real-world sized instances.
Keywords: 650; Scheduling; Moving assembly line; Walking time; Material placement; Mixed-model production